PROSPECTS FOR THE FORMATION OF OIL AND GAS TOURIST DESTINATIONS - Zapukhliak, Ivanna Bogdanivna; Вербовська, Леся Степанівна; Сохан, Олег Володимирович (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2022)
The article considers the need to produce innovative types of tourism that would combine work and rest, perform a cognitive and educational function in combination with health and recreation. It is justified that at the request of the modern tourist and his / her needs it is expedient to form tourist destinations as separate territories that are attractive due to specific infrastructure and opportunities to offer a unique tourist service, product, satisfying a combination of the most diverse needs of the traveler. The study of the "tourist service" concept content and types of tourist products became the basis for the formation of the concept of "oil and gas tourist destination". The main features of the tourist destination and the prerequisites for the formation of oil and gas tourist destinations are given. Subjects of the oil and gas industry of Ukraine, regions of oil and gas deposits, and opportunities to develop an innovative type of tourism within regional tourist oil and gas destinations are considered. It has been proven that having a significant health and medical infrastructure, having various gyms, drilling exhibitions, oil and gas industry museums, squares with rocking machines models, etc., it is worth talking about the further development of this unique infrastructure in the form of tourist destinations with the aim of offering a wide the circle of travelers (students, scientists, practitioners) of innovative tourist products; promoting the relevance of engineering knowledge and earth sciences; demonstration of modern trends in energy in general, and the oil and gas industry in particular; formation of a platform for gaining practical experience. It was established that the advantage of creating tourist destinations of the oil and gas complex for the traveler is the combination of the process of acquiring new knowledge and practical skills with rest and recovery, for the region - development due to the formation of new unique tourist products within the tourist destination, for oil and gas enterprises - the development of a new type of activity, obtaining additional profits, popularization of oil and gas professions.